2018
DOI: 10.3847/1538-4357/aabae9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Evolution of Non-thermal Electrons in Solar Flares Using 3D Modeling

Abstract: Understanding nonthermal particle generation, transport, and escape in solar flares requires detailed quantification of the particle evolution in the realistic 3D domain where the flare takes place. Rather surprisingly, apart of standard flare scenario and integral characteristics of the nonthermal electrons, not much is known about actual evolution of nonthermal electrons in the 3D spatial domain. This paper attempts to begin to remedy this situation by creating sets of evolving 3D models, the synthesized emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Indeed, we found that the electrons are accelerated promptly (the acceleration time is shorter than 50 ms) up to several hundreds of keV, which is difficult to reconcile with conventual stochastic acceleration models. These electrons propagate freely along the flux tube, which implies no (or only weak) wave-particle interaction unlike many other cases (e.g., Fleishman et al 2018), where turbulence was found to play a central role in particle acceleration and transport. On the other side the observations are broadly consistent with the predictions of models that invoke large, super-Dreicer, electric fields.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, we found that the electrons are accelerated promptly (the acceleration time is shorter than 50 ms) up to several hundreds of keV, which is difficult to reconcile with conventual stochastic acceleration models. These electrons propagate freely along the flux tube, which implies no (or only weak) wave-particle interaction unlike many other cases (e.g., Fleishman et al 2018), where turbulence was found to play a central role in particle acceleration and transport. On the other side the observations are broadly consistent with the predictions of models that invoke large, super-Dreicer, electric fields.…”
Section: Discussionmentioning
confidence: 93%
“…Closed flaring flux tubes can represent rather large reservoirs of highenergy electrons located either nearby (Kuroda et al, 2018) or far away from Fleishman et al (Fleishman et al, 2017) the main flare acceleration sites, possibly providing the seed population for solar energetic particles (SEPs). Fleishman et al (2011Fleishman et al ( , 2013Fleishman et al ( , 2016a probed the acceleration sites using MW observations and concluded that the acceleration regime was consistent with stochastic acceleration, while Fleishman et al (2018b) extended in time the studies of Fleishman et al (2016b) and Kuroda et al (2018) to quantify the acceleration and transport of the nonthermal electrons in the 3D domain. In all of these studies, broadband MW spectroscopy and imaging have been crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Also field-aligned currents can be driven by pressure gradient and flow shear. In the solar flare loops with the large loss-cone Eradat Oskoui et al ( 2014) such long trapping of energetic particles would require pitch-angle scattering away from the loss-cone, i.e., would require strong turbulence level (see discussion in Fleishman et al (2018Fleishman et al ( , 2020). Alternatively, energetic particle population can be continuously supplemented by series of transient energy releases.…”
Section: Energetic Particle Fluxes and Their Correlation With Currentsmentioning
confidence: 99%